La motivación docente en el rendimiento escolar de los niños/as del primer grado de educación general básica de la escuela fiscal Miguel Riofrío nº 1 de la ciudad de Loja, periodo lectivo 2013 – 2014 - Benítez Granda, Mayra Beatriz (2014)
This research refers to the "Teacher s motivation on the schoolchildren performance of the first grade students of Elementary School at the Fiscal School Miguel Riofrío No 1 from Loja City, during the school year 2013 - 2014." This work is theoretically grounded by two categories: The first one deal with teachers motivation, with concepts, types and importance; and the second one is related to the academic performance, definition, process, types, factors and other factors. To elaborate this research the main objective was formulated: To determine how the teacher s motivation influences on the academic performance of the students of the first grade of Elementary Education at the Fiscal School Miguel Riofrío No 1 from Loja City, during the school year 2013 - 2014. The research is based in a non-experimental design, so it takes the logic way, allowing questioning the reality in order to describe the information, verifying and proving the objectives and establishing the proper conclusions and recommendations. The methods used were scientific, deductive, inductive, bibliographic, analytic-synthetic and statlstical. The employed techniques were the survey for the teachers, and the observation guide for the students. The research was done with a population of 60 students and 3 teachers. Once the results were taken, the mentioned instruments were applied and the conclusion was: The 3 teachers who represent the 100% of the teachers population, belleved that sometimes they use different motivation techniques, and they consider that the development of the class is important during the learning process, and if it is not developed it is hard to achieve the best outcomes in school performance, and it Was also determined that the teachers motivation definitely influences in the learning process of the girls and boys of the Elementary School at the Fiscal School Miguel Riofrío No 1. From the observation guide applled to the students, it seems that a low percentage shows difficulties in the different areas of knowledge, but some classes demonstrate a limited child development and growth and they showed few interest in the people around them during the development of the activities, not paying attention to the teacher or not trying to communicate with her, they also showed a shy and introverted behavior what bring them to have low grades at school, also the teacher didnt motivate them during the class, Therefore it is recommended that the teachers have to plan and implement each of their classes using different kinds of motivation according to the characteristics of each area, and also they have to use all the didactic material needed for each activity inside or outside the classroom. As a conclusion: teacher s motivation is important in the social development of the students.